Results From 10 Years of Interprofessional Training on Motivational Interviewing. (June 2017) - Cook, Paul F.; Manzouri, Saman; Aagaard, Laurra; O'Connell, Lindsay; Corwin, Marla; Gance-Cleveland, Bonnie
Motivational interviewing (MI) is a popular evidence-based method to support health behavior change. We examined evaluations from 10 years of interprofessional workshops on MI to identify trends in trainees' MI-related knowledge, attitude, and behavior. From 2006 to 2015, 394 trainees participated in continuing education MI workshops with our team and completed a validated posttraining questionnaire. Participants were 90% female and 66% White, with M = 12 years in practice. They worked in pediatric and adult care; urban and rural locations; and inpatient, outpatient, and nonhealth settings. The largest groups were nurses (20%), allied health professionals (20%), and health educators or case managers (15%). Trainees' professional diversity increased over time, their average age and years in practice decreased, and the percentage with prior MI training increased. Practitioners in telehealth and nonhealth settings had lower scores overall. Outcomes varied significantly by professional discipline: Mental health professionals, case managers, health educators, and nurses had higher scores on some outcome variables than nonhealth professionals. Years of clinical experience predicted MI-consistent attitude, but prior training, other demographic variables, and training process variations had no consistent effects. Although many trainees had already received MI training, outcome measures showed room for improvement. MI presents continued opportunities for interprofessional education.